Patterns of periodontal disease progression based on linear mixed models of clinical attachment loss - Teles, Ricardo; Moss, Kevin; Preisser, John S.; Genco, Robert; Giannobile, William V.; Corby, Patricia; Garcia, Nathalia; Jared, Heather; Torresyap, Gay; Salazar, Elida; Moya, Julie; Howard, Cynthia; et al. (Journal of clinical periodontology, 2018)
Aim The goal of the present longitudinal cohort study was to examine patterns of periodontal disease progression at progressing sites and subjects defined based on linear mixed models (LMM) of clinical attachment loss (CAL). Materials and Methods A total of 113 periodontally healthy and 302 periodontitis subjects had their CAL calculated bimonthly for 12 months. LMMs were fitted for each site and the predicted CAL levels used to categorize their progression state. Participants were grouped based on the number of progressing sites into unchanged, transitional and active subjects. Patterns of periodontal disease progression were explored using descriptive statistics. Results Progression occurred primarily at molars (50% of progressing sites) and inter‐proximal sites (72%), affected a higher proportion of deep than shallow sites (2.7% versus 0.7%), and pocketing was the main mode of progression (49%). We found a low level of agreement (47%) between the LMM and traditional approaches to determine progression such as change in CAL ≥3 mm. Fourteen per cent of subjects were classified as active and among those 93% had periodontitis. The annual mean rate of progression for the active subjects was 0.35 mm/year. Conclusion Progressing sites and subjects defined based on LMMs presented patterns of disease progression similar to those previously reported in the literature.